Extraordinary Delayed-Onset Negative Pressure Pulmonary Hemorrhage Resulting in Cardiac Arrest after General Anesthesia for Vocal Cord Polypectomy - Masahiro Koide; Tatsuya Kitada; Masaya Kogure; Kento Fukui; Koji Sogabe; Yukinori Kato; Hiroki Kitajima; Satoshi Akabame (Case Reports in Critical Care, 2020)
Negative pressure pulmonary edema and hemorrhage are uncommon but potentially life-threatening complications associated with general anesthesia. Postoperative negative pressure pulmonary edema usually occurs immediately after surgery, and delayed-onset cases occurring more than 1 hour after surgery have rarely been reported. A 37-year-old woman with bronchial asthma underwent vocal cord polypectomy under general anesthesia in another hospital and experienced cardiac arrest due to a negative pressure pulmonary hemorrhage occurring 3 hours and 30 minutes after surgery. She was successfully treated with venoarterial extracorporeal membrane oxygenation and completely recovered without any complications. Extraordinary delayed-onset negative pressure pulmonary hemorrhage occurring more than three hours after surgery has rarely been reported. This case may indicate the need for more careful observation of patients following surgery.